Anatomical Cadaver Study of Endolaryngeal Vascularization: Focus on the Glottis, Supraglottis, and Subglottis From the Transoral Microsurgical Point of View - Perotti, Pietro; Ferrari, Marco; Montalto, Nausica; Lancini, Davide; Paderno, Alberto; Incandela, Fabiola; Buffoli, Barbara; Rodella, Luigi Fabrizio; Piazza, Cesare (Frontiers in Oncology, 2018)
Introduction: Carbon dioxide laser coagulation during transoral laser microsurgery (TLM) for laryngeal cancer allows control of bleeding from vessels smaller than 0.5 mm. Therefore, larger arteries and veins must be carefully managed by clipping and/or monopolar cautery. The aim of this paper is to detail endolaryngeal vascular anatomy and identify areas of possible bleeding during TLM. Methods: We performed an anatomical study on a series of 11 fresh-frozen human cadavers. After injection of a bicomponent red silicone into the innominate, left common carotid, and left subclavian arteries, 22 hemilarynges were dissected, the course of the supraglottic, glottic, and subglottic vessels were traced after microdissection of the intervening structures, and their size measured at specific landmark points where such vessels are more frequently encountered during TLM. Results: Three vessels arising from the superior laryngeal artery were identified after its entry point at the level of the thyro-hyoid membrane: 1) the epiglottic artery (EA), documented in 100% of cases, and a common trunk dividing into two main vessels 2) the postero-inferior artery (PIA), present in 100% of the specimens, running downward and dividing in a posterior (pPIA) and anterior (aPIA) branches 3) the antero-inferior artery (AIA), present in 95% of our specimens, running downward to the anterior commissure (AC). Two transverse anastomotic networks (TANs) connected the AIA and PIA, both parallel to the vocal muscle, one lateral (present in 100% of cases), and another medial (91% of specimens). Finally, a fourth vessel supplying the glottic plane was found to be the endolaryngeal paracommissural branch of the cricothyroid artery (PCA), arising from the inferior laryngeal artery and emerging just below the AC, through the crico-thyroid membrane (reported in 100% of the specimens). This vessel anastomosed in 91% of cases with the AIA, through one or both of the TANs. Conclusion: The precise course of the endolaryngeal arteries, their relationships with adjacent structures, and size at specific landmark points have been herein described in order to provide surgeons with a map to guide them during the steep learning curve of transoral surgery of the larynx, with special emphasis given to TLM.